A Relationship Assessment Between Environmental Practices, Corporate Value, and CSR in Sustainability Context - Astuti, Tri; Magdalena, Maria; Mandagie, Yuana Rizky; Irawan, Tedhi (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2024)
AbstractThis study examines the influence of environmental performance disclosure within corporate social responsibility on company value. It assesses the impact of green intellectual capital (human, structural, and relational), green innovation (product and process), carbon emission disclosure, and eco-efficiency on Price Book Value (PBV). The sample includes 11 companies from the Sri Kehati Index 2018-2022, which apply Sustainable Responsible Investment (SRI) and ESG principles. Using multiple regression analysis, the findings reveal that green intellectual capital disclosure does not significantly affect company value. However, green innovation positively impacts PBV, suggesting its importance in enhancing corporate valuation. In contrast, carbon emission disclosure and eco-efficiency are found to negatively influence PBV. These results highlight the critical role of green innovation in driving company value while suggesting that certain environmental disclosures may lower valuations. The study provides valuable insights into how environmental practices affect corporate value within the framework of corporate social responsibility and sustainability. Keywords:Green Intellectual Capital, Green Innovation, Carbon Emissions Disclosure, Eco-Efficiency, Company Value